Graphite material for graphite boat sheet and preparation method thereof

By purifying and acidic oxidizing natural scale graphite, and introducing zirconium oxide into hydrothermal reaction, combining thiolation and grafting reactions, high-performance graphite materials were prepared, which solved the problems of uneven coating of graphite boat sheets and short service life, and achieved higher conductivity, mechanical properties, and lower porosity and thermal expansion coefficient.

CN118579774BActive Publication Date: 2025-03-18HUBEI DONGNANJIA ADVANCED CARBON MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410738780.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-03-18
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

After repeated use of existing graphite boat sheets, the coating is uneven, and the silicon wafers and boat walls may burst and peel off, resulting in a reduced coating efficiency and short service life.

Method used

By purifying natural scale graphite, acid oxidizing treatment, and introducing zirconia into hydrothermal reaction, followed by thiolation and grafting reaction, and finally uniformly mixing with petroleum coke and asphalt coke, graphite material with high conductivity, mechanical properties and low expansion coefficient was prepared.

Benefits of technology

It improves the conductive and mechanical properties of graphite materials, reduces porosity and thermal expansion coefficient, extends the service life of graphite boat sheets, and improves the stability and efficiency of coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004882574110000151
    Figure BDA0004882574110000151
Patent Text Reader

Abstract

The invention discloses a graphite material for graphite boat sheets and a preparation method thereof, comprising the following steps: S1, pretreatment of natural flake graphite; S2, preparation of modified flake graphite; S3, preparation of mixed material; S4, crushing and grinding; S5, pressing and roasting; S6, impregnation and carbonization; S7, graphitization. The graphite material is prepared by modifying natural flake graphite, and the natural flake graphite has good electrical conductivity and thermal conductivity, which can not only improve the comprehensive performance of the graphite material, but also avoid the problems of large porosity, low mechanical strength, poor oxidation resistance and thermal shock resistance of the graphite material due to the poor compatibility of natural flake graphite with petroleum coke and asphalt coke, so that the prepared graphite material not only has good thermal conductivity, but also has good mechanical properties and low expansion coefficient, and is particularly suitable for preparing graphite boat sheets, thereby improving the service life of the graphite boat sheets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite materials, and in particular relates to a graphite material for a graphite boat sheet and a preparation method thereof. Background Art

[0002] The current production process of solar cells mainly includes texturing, diffusion, etching, coating, printing and sintering, among which the coating is mainly achieved by plasma enhanced chemical vapor deposition (PECVD). The PECVD method is simple to operate, has good repeatability and low cost. Compared with liquid phase epitaxy (LPE), metal organic chemical vapor deposition (MOCVD), molecular beam epitaxy (MBE), vapor phase epitaxy (VPE) and other methods, the silicon nitride film prepared by it has technical advantages such as high strength, high hardness, large dielectric constant, adjustable refractive index, high transmittance, small light attenuation coefficient and good chemical stability. The use of tubular PECVD method for coating process can achieve higher coating efficiency. The graphite boat is the carrier for coating the silicon wafer in the solar cell. When coating, the graphite boat with the uncoated silicon wafer inserted is sent into the cavity of the PECVD vacuum coating equipment and the PECVD process is used for discharge coating.

[0003] With the growing demand for cost reduction and efficiency improvement in the photovoltaic market, the production capacity of tubular PECVD equipment is also increasing. As a key loading tool in the tubular PECVD production process, the number of silicon wafers coated in a single large-capacity graphite boat has increased from the original 300 or 400 to about 600 now, and the length of the boat has reached more than 2 meters, so the performance requirements for the graphite boat are gradually increasing.

[0004] Generally, when selecting graphite boat materials, the following points should be considered: 1. High density and low porosity, especially fewer open pores; 2. Good electrical conductivity, especially stable resistivity under high temperature conditions; 3. Uniform material, especially to avoid various defects such as cracks, sand holes and deformation; 4. Higher purity. Graphite boat sheets are used under high temperature and high vacuum. If there are more impurities, a large amount of volatile substances will be easily formed at high temperature, which will not only increase the coating pretreatment time and affect production efficiency, but also affect the quality of some special products; 5. Lower thermal expansion coefficient and good seismic resistance to ensure stable size and good contact, and not to break under rapid cooling and heating; 6. Good mechanical strength to reduce breakage during operation.

[0005] Chinese patent CN115287632A discloses a graphite boat pretreatment method and a modified graphite boat, the pretreatment method comprising the following steps: (1) subjecting the graphite boat to a constant temperature treatment and a vacuum heating treatment; (2) subjecting the graphite boat treated in step (1) to a composite deposition coating treatment; (3) subjecting the graphite boat treated in step (2) to a vacuum and then introducing nitrogen, exiting the boat, and completing the pretreatment; the composite deposition coating treatment in step (2) comprises depositing an inner layer of silicon oxide and an outer layer of silicon nitride on the surface. Through the pretreatment before the existing saturation process, a dense inner layer of silicon oxide and an outer layer of silicon nitride with a stable film surface are coated on the surface of the graphite boat, which, on the one hand, prevents the graphite boat from overflowing with impurities, and at the same time can reduce the pollution of aluminum oxide during back coating, improve the uniformity of the aluminum oxide film, and reduce the occurrence of dark edges. However, this patent processes the graphite boat by coating, which may lead to uneven coating, cracking and peeling of silicon wafers and boat walls, reduced coating rate, and even inability to continue coating after the graphite boat is reused many times.

[0006] Therefore, there is an urgent need in the art to develop a high-performance graphite material for graphite boats to increase the service life of the graphite boats. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a graphite material for graphite boat sheets and a preparation method thereof. The graphite material has good thermal conductivity as well as good mechanical properties and a low expansion coefficient, and is particularly suitable for preparing graphite boat sheets, thereby increasing the service life of the graphite boat sheets.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A method for preparing a graphite material for a graphite boat sheet comprises the following steps:

[0010] S1, pretreatment of natural flake graphite: purifying natural flake graphite and adding it into an acidic potassium permanganate solution for stirring and impregnation treatment, filtering, washing and drying after the treatment to obtain pretreated natural flake graphite;

[0011] S2, preparation of modified flake graphite: adding the pretreated natural flake graphite in step S1 to deionized water, then adding zirconium oxychloride, stirring evenly, adding ammonia water, carrying out hydrothermal reaction, filtering, washing, and drying after the reaction is completed to obtain solid powder; then adding the solid powder to anhydrous ethanol, then adding γ-mercaptopropyltrimethoxysilane, stirring at 50-60° C. for 2-3 hours, then adding 1-dodecene and benzophenone, carrying out isothermal reaction under ultraviolet light, filtering, washing, and drying after the reaction is completed to obtain modified flake graphite;

[0012] S3, preparation of a mixture: grinding petroleum coke and asphalt coke to obtain a mixed powder, then adding the mixed powder and carbon black into a kneading pot and mixing them evenly, performing a primary kneading process; then adding the modified flake graphite in step S2, mixing them evenly, performing a secondary kneading process, and obtaining a mixture;

[0013] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it twice to obtain abrasive;

[0014] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine for pressing to obtain a green body, and then calcining the green body to obtain a calcined material;

[0015] S6, impregnation and carbonization: adding the roasted material in step S5 into an impregnation tank, evacuating the tank, and then adding molten medium-temperature asphalt for impregnation, and carbonizing the material after the impregnation to obtain a carbonized material;

[0016] S7, graphitization: graphitizing the carbonized material in step S6 to obtain the graphite material for the graphite boat.

[0017] Preferably, the pH of the acidic potassium permanganate solution in step S1 is 3-4, the concentration of potassium permanganate is 40-60 g / L, the temperature of the stirring immersion is 30-40° C., and the time is 2-4 h.

[0018] More preferably, the purification process of the natural flake graphite in step S1 is: adding the natural flake graphite to a sodium hydroxide solution with a concentration of 0.5-1 mol / L, immersing it at 40-50°C for 1-2h, filtering and drying after immersion, calcining at 500°C for 2h, then adding it to a hydrochloric acid solution with a mass concentration of 10%, immersing it at a microwave power of 500W for 1h, filtering, washing and drying after immersion.

[0019] In the present invention, natural flake graphite is purified to increase the carbon content of the natural flake graphite, and is used as a raw material, so that the prepared graphite material has better electrical conductivity, and the problem of large porosity caused by impurities during graphitization can also be reduced. Subsequently, the purified natural flake graphite is subjected to acid oxidation treatment to increase the active oxygen-containing functional groups on the surface of the natural flake graphite, thereby improving the binding force between the natural flake graphite and petroleum coke and asphalt coke, thereby improving the mechanical properties of the graphite material.

[0020] Preferably, in step S2, the mass concentration of the ammonia water is 10-15%, the mass ratio of the pretreated natural flake graphite, deionized water, zirconium oxychloride, and ammonia water is 50:800-1000:20-30:60-100, the temperature of the hydrothermal reaction is 140-170°C, and the time is 7-10h; the mass ratio of the solid powder, γ-mercaptopropyltrimethoxysilane, 1-dodecene, and benzophenone is 50:5-8:4-8:0.2-0.5, and the intensity of the ultraviolet light is 20-40W / m 2 The temperature of the isothermal reaction is 60-70°C and the time is 1-2h.

[0021] In the present invention, natural flake graphite is modified to introduce zirconium oxide on the surface, followed by mercapto treatment with silane, and finally grafted with 1-dodecene. The introduction of zirconium ions can generate zirconium carbide in the subsequent graphitization process of the graphite material, thereby improving the hardness of the graphite material. Meanwhile, zirconium carbide also has an extremely high melting point, thereby improving the heat resistance of the graphite material and increasing the service life of the graphite material. The introduced 1-dodecene contains long-chain alkanes and has good compatibility with petroleum coke and asphalt coke. During the kneading process, the petroleum coke, asphalt coke and natural flake graphite can be completely compatible, thereby further improving the comprehensive performance of the flake graphite in the graphite material. Moreover, the 1-dodecene has stronger hydrophobicity after carbonization, and during the subsequent asphalt impregnation, the flake graphite has better affinity with the asphalt, thereby enabling the asphalt to better coat the roasted material and improving the mechanical properties of the graphite material.

[0022] Preferably, in step S3, the mass ratio of petroleum coke to asphalt coke is 20:25-60, and the mass ratio of the mixed powder, carbon black and modified flake graphite is 45-80:10-20:15-30; the temperature of the first kneading treatment is 90-100°C, and the time is 0.5-1h, and the temperature of the second kneading treatment is 160-180°C, and the time is 0.5-1h.

[0023] More preferably, in step S3, the mass ratio of petroleum coke to asphalt coke is 20:30-50, and the mass ratio of the mixed powder, carbon black and modified flake graphite is 50-70:15-20:20-25; the temperature of the first kneading treatment is 95-100°C, and the time is 0.5-1h, and the temperature of the second kneading treatment is 170-180°C, and the time is 0.5-1h.

[0024] Preferably, the particle size of the abrasive in step S4 is 5-15 μm.

[0025] More preferably, the particle size of the abrasive in step S4 is 5-10 μm.

[0026] Preferably, the pressing pressure in step S5 is 90-130 MPa and the time is 1-2 h; the calcination temperature is 750-850° C. and the time is 3-5 days.

[0027] More preferably, the pressing pressure in step S5 is 110-130 MPa, and the time is 1-1.5 h; the calcination temperature is 800-850° C., and the time is 3-4 days.

[0028] Preferably, in step S6, the vacuum is evacuated to 60-100 Pa, and the immersion conditions are 190-210° C. and 4-7 MPa for 15-20 h; the carbonization temperature is 1100-1300° C., and the time is 20-30 days.

[0029] More preferably, in step S6, the vacuum is evacuated to 60-80 Pa, and the immersion conditions are 200-210° C. and 5-7 MPa for 15-18 h; the carbonization temperature is 1200-1300° C. and the time is 20-25 days.

[0030] Preferably, the graphitization temperature in step S7 is 2500-2900° C. and the time is 30-40 days.

[0031] More preferably, the graphitization temperature in step S7 is 2600-2800° C. and the time is 30-35 days.

[0032] The present invention also protects a graphite material for a graphite boat sheet prepared by the method as described above.

[0033] The present invention also protects the use of the graphite material as described above in preparing graphite boat sheets.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The graphite material for graphite boat provided by the present invention is prepared by modifying natural flake graphite as a raw material. The natural flake graphite has good electrical and thermal conductivity, which can not only improve the comprehensive performance of the graphite material, but also avoid the problems of large porosity, low mechanical strength, poor oxidation resistance and thermal shock resistance of the graphite material due to the poor compatibility of natural flake graphite with petroleum coke and asphalt coke. The prepared graphite material not only has good thermal conductivity, but also has good mechanical properties and low expansion coefficient, and is particularly suitable for preparing graphite boats, thereby improving the service life of the graphite boats.

[0036] (2) The graphite material for graphite boat provided by the present invention is to purify natural flake graphite and then acid-oxidize it to increase the number of active oxygen groups on the surface of the flake graphite, which can not only improve the bonding strength between the flake graphite and petroleum coke and asphalt coke, but also facilitate subsequent reactions; then zirconium oxide is in situ generated on the surface of the flake graphite by a hydrothermal method, thereby introducing zirconium, which can improve the heat resistance of the graphite material in the subsequent graphitization process, thereby improving the thermal shock resistance of the graphite material and reducing the expansion coefficient; then the flake graphite is modified with γ-mercaptopropyltrimethoxysilane, on the one hand, the introduced silane makes the flake graphite have better dispersibility, and on the other hand, the introduced mercapto group is conducive to the next reaction; finally, the mercaptolated flake graphite is reacted with 1-dodecene to introduce long-chain alkanes on the surface of the flake graphite, and during the kneading process, the petroleum coke, asphalt coke and natural flake graphite can be completely compatible, further improving the comprehensive performance of the flake graphite in the graphite material. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the present invention, natural flake graphite was purchased from Qingdao Mingrun Chenyue Graphite Co., Ltd., with a mesh size of 800 mesh;

[0039] Petroleum coke: particle size is -300 mesh, moisture ≤1%, ash ≤1%, low-sulfur cooked coke block;

[0040] Asphalt coke: particle size -300 mesh, moisture ≤1%, ash ≤1%, true density ≥1.98g / cm 3 , using low-sulfur coke blocks;

[0041] Medium temperature asphalt: softening point is 83-88℃, coking value is ≥48%, quinoline insoluble matter is ≤0.30%.

[0042] Example 1

[0043] A method for preparing a graphite material for a graphite boat sheet, characterized in that it comprises the following steps:

[0044] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3.5, potassium permanganate concentration of 50g / L), stirred and impregnated at 35°C for 3h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;

[0045] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 was added to 900g of deionized water, followed by adding 25g of zirconium oxychloride, stirring evenly, adding 80g of ammonia water with a mass concentration of 13%, and hydrothermally reacting at 160°C for 8h. After the reaction was completed, filtering, washing and drying were performed to obtain a solid powder; then 50g of the solid powder was added to 800g of anhydrous ethanol, followed by adding 7g of γ-mercaptopropyltrimethoxysilane, stirring at 55°C for 2.5h, and then adding 7g of 1-dodecene and 0.4g of benzophenone, and heating at 30W / m 2 Under ultraviolet light, the reaction was carried out at a constant temperature of 65°C for 1.5 hours. After the reaction was completed, the modified flake graphite was filtered, washed and dried to obtain;

[0046] S3, preparation of a mixture: 200g of petroleum coke and 400g of asphalt coke were ground to 60 mesh to obtain a mixed powder, and then 600g of the mixed powder and 150g of carbon black were added to a kneading pot and mixed evenly, and kneaded at 950°C for 1h; then 250g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 170°C for 1h to obtain a mixture;

[0047] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for the second time to obtain abrasive, the particle size of the abrasive is 5-15 μm;

[0048] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine, pressing at 110 MPa for 1.5 hours to obtain a green body, and then calcining the green body at 800° C. for 4 days to obtain a calcined material;

[0049] S6, impregnation and carbonization: add the roasted material in step S5 into an impregnation tank, evacuate to 80Pa, then add molten medium-temperature asphalt, impregnate at 200°C and 6MPa for 18h, and after impregnation, carbonize at 1200°C for 25 days to obtain a carbonized material;

[0050] S7, graphitization: graphitizing the carbonized material in step S6 at 2700° C. for 35 days to obtain the graphite material for the graphite boat.

[0051] Example 2

[0052] A method for preparing a graphite material for a graphite boat sheet, characterized in that it comprises the following steps:

[0053] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3.5, potassium permanganate concentration of 50g / L), stirred and impregnated at 35°C for 3h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;

[0054] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 was added to 900g of deionized water, followed by adding 25g of zirconium oxychloride, stirring evenly, adding 70g of ammonia water with a mass concentration of 15%, and hydrothermally reacting at 150°C for 9h. After the reaction was completed, filtering, washing, and drying were performed to obtain a solid powder; then 50g of the solid powder was added to 800g of anhydrous ethanol, followed by adding 6g of γ-mercaptopropyltrimethoxysilane, stirring at 55°C for 2.5h, and then adding 6g of 1-dodecene and 0.3g of benzophenone, and heating at 25W / m 2 Under ultraviolet light, the reaction was carried out at a constant temperature of 65°C for 1.5 hours. After the reaction was completed, the modified flake graphite was filtered, washed and dried to obtain;

[0055] S3, preparation of a mixture: 200g of petroleum coke and 500g of asphalt coke were ground to 60 mesh to obtain a mixed powder, and then 700g of the mixed powder and 150g of carbon black were added to a kneading pot and mixed evenly, and kneaded at 95°C for 0.5h; then 200g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 170°C for 0.5h to obtain a mixture;

[0056] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for the second time to obtain abrasive, the particle size of the abrasive is 5-15 μm;

[0057] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine, pressing at 100 MPa for 1.5 hours to obtain a green body, and then calcining the green body at 800° C. for 4 days to obtain a calcined material;

[0058] S6, impregnation and carbonization: add the roasted material in step S5 into an impregnation tank, evacuate to 80Pa, then add molten medium-temperature asphalt, impregnate at 200°C and 5MPa for 17h, and after impregnation, carbonize at 1200°C for 25 days to obtain a carbonized material;

[0059] S7, graphitization: graphitizing the carbonized material in step S6 at 2800° C. for 35 days to obtain the graphite material for the graphite boat.

[0060] Example 3

[0061] A method for preparing a graphite material for a graphite boat sheet, characterized in that it comprises the following steps:

[0062] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.5mol / L, impregnated at 40°C for 2h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 4, potassium permanganate concentration of 40g / L), stirred and impregnated at 30°C for 4h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;

[0063] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 was added to 800g of deionized water, followed by adding 20g of zirconium oxychloride, stirring evenly, adding 60g of ammonia water with a mass concentration of 15%, and hydrothermally reacting at 140°C for 10h. After the reaction was completed, filtering, washing and drying were performed to obtain a solid powder; then 50g of the solid powder was added to 800g of anhydrous ethanol, followed by adding 5g of γ-mercaptopropyltrimethoxysilane, stirring at 50°C for 3h, and then adding 5g of 1-dodecene and 0.2g of benzophenone, and heating at 20W / m 2 Under ultraviolet light, the reaction was carried out at a constant temperature of 60°C for 2 hours. After the reaction was completed, the modified flake graphite was filtered, washed and dried to obtain the modified flake graphite.

[0064] S3, preparation of a mixture: 200g of petroleum coke and 250g of asphalt coke were ground to 60 mesh to obtain a mixed powder, and then 450g of the mixed powder and 100g of carbon black were added to a kneading pot and mixed evenly, and kneaded at 90°C for 1h; then 150g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 160°C for 1h to obtain a mixture;

[0065] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for the second time to obtain abrasive, the particle size of the abrasive is 5-15 μm;

[0066] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine, pressing at 90 MPa for 2 h to obtain a green body, and then calcining the green body at 750° C. for 5 days to obtain a calcined material;

[0067] S6, impregnation and carbonization: add the roasted material in step S5 into an impregnation tank, evacuate to 60Pa, then add molten medium-temperature asphalt, impregnate at 190°C and 4MPa for 20h, and after impregnation, carbonize at 1100°C for 30 days to obtain a carbonized material;

[0068] S7, graphitization: graphitizing the carbonized material in step S6 at 2500° C. for 40 days to obtain the graphite material for the graphite boat.

[0069] Example 4

[0070] A method for preparing a graphite material for a graphite boat sheet, characterized in that it comprises the following steps:

[0071] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 1mol / L, impregnated at 50°C for 1h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 4, potassium permanganate concentration of 60g / L), stirred and impregnated at 40°C for 2h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;

[0072] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 is added to 1000g of deionized water, followed by adding 30g of zirconium oxychloride, stirring evenly, adding 100g of ammonia water with a mass concentration of 10%, and hydrothermally reacting at 170°C for 7h. After the reaction is completed, filtering, washing and drying are performed to obtain a solid powder; then 50g of the solid powder is added to 800g of anhydrous ethanol, followed by adding 8g of γ-mercaptopropyltrimethoxysilane, stirring at 60°C for 2h, and then adding 8g of 1-dodecene and 0.5g of benzophenone, and heating at 40W / m 2 Under ultraviolet light, the reaction was carried out at a constant temperature of 70°C for 1 hour. After the reaction was completed, the modified flake graphite was filtered, washed and dried to obtain the modified flake graphite.

[0073] S3, preparation of a mixture: 200g of petroleum coke and 600g of asphalt coke were ground to 60 mesh to obtain a mixed powder, and then 800g of the mixed powder and 200g of carbon black were added to a kneading pot and mixed evenly, and kneaded at 100°C for 0.5h; then 300g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 180°C for 0.5h to obtain a mixture;

[0074] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for the second time to obtain abrasive, the particle size of the abrasive is 5-15 μm;

[0075] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine, pressing at 130 MPa for 1 hour to obtain a green body, and then calcining the green body at 850° C. for 3 days to obtain a calcined material;

[0076] S6, impregnation and carbonization: add the roasted material in step S5 into an impregnation tank, evacuate to 100 Pa, then add molten medium-temperature asphalt, impregnate at 210° C. and 7 MPa for 15 h, and after the impregnation is completed, carbonize at 1300° C. for 20 days to obtain a carbonized material;

[0077] S7, graphitization: graphitizing the carbonized material in step S6 at 2900° C. for 30 days to obtain the graphite material for the graphite boat.

[0078] Comparative Example 1

[0079] A method for preparing a graphite material for a graphite boat sheet, characterized in that it comprises the following steps:

[0080] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3.5, potassium permanganate concentration of 50g / L), stirred and impregnated at 35°C for 3h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;

[0081] S2, preparation of a mixture: 200g of petroleum coke and 400g of asphalt coke were ground to 60 mesh to obtain a mixed powder, and then 600g of the mixed powder and 150g of carbon black were added to a kneading pot and mixed evenly, and kneaded at 950°C for 1h; then 250g of the pretreated natural flake graphite in step S1 was added, mixed evenly, and kneaded at 170°C for 1h to obtain a mixture;

[0082] S3, crushing and grinding: crushing the mixed material in step S2 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;

[0083] S4, pressing and calcining: adding the abrasive in step S3 into a press, pressing at 110 MPa for 1.5 h to obtain a green body, and then calcining the green body at 800° C. for 4 days to obtain a calcined material;

[0084] S5, impregnation and carbonization: add the roasted material in step S4 into an impregnation tank, evacuate to 80Pa, then add molten medium-temperature asphalt, impregnate at 200°C and 6MPa for 18h, and after impregnation, carbonize at 1200°C for 25 days to obtain a carbonized material;

[0085] S6, graphitization: graphitizing the carbonized material in step S5 at 2700° C. for 35 days to obtain the graphite material for the graphite boat.

[0086] Comparative Example 2

[0087] A method for preparing a graphite material for a graphite boat sheet, characterized in that it comprises the following steps:

[0088] S1, preparation of modified flake graphite: 50g of natural flake graphite in step S1 is added to 900g of deionized water, followed by adding 25g of zirconium oxychloride, stirring evenly, adding 80g of 13% ammonia water, and hydrothermally reacting at 160°C for 8h. After the reaction is completed, filtering, washing, and drying to obtain modified flake graphite;

[0089] S2, preparation of a mixture: 200g of petroleum coke and 400g of asphalt coke were ground to 60 mesh to obtain a mixed powder, and then 600g of the mixed powder and 150g of carbon black were added to a kneading pot and mixed evenly, and kneaded at 950°C for 1h; then 250g of the modified flake graphite in step S1 was added, mixed evenly, and kneaded at 170°C for 1h to obtain a mixture;

[0090] S3, crushing and grinding: crushing the mixed material in step S2 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;

[0091] S4, pressing and calcining: adding the abrasive in step S3 into a press, pressing at 110 MPa for 1.5 h to obtain a green body, and then calcining the green body at 800° C. for 4 days to obtain a calcined material;

[0092] S5, impregnation and carbonization: add the roasted material in step S4 into an impregnation tank, evacuate to 80Pa, then add molten medium-temperature asphalt, impregnate at 200°C and 6MPa for 18h, and after impregnation, carbonize at 1200°C for 25 days to obtain a carbonized material;

[0093] S6, graphitization: graphitizing the carbonized material in step S5 at 2700° C. for 35 days to obtain the graphite material for the graphite boat.

[0094] The graphite materials prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, wherein the bulk density was tested with reference to GB / T 24528-2009 "Determination Method for Bulk Density of Carbon Materials", the Shore hardness was tested with reference to GB / T 39535-2020 "Determination Method for Shore Hardness of Carbon Materials", the flexural strength was tested with reference to GB / T 3074.1-2021 "Determination Method for Flexural Strength of Carbon Materials", the compressive strength was tested with reference to GB / T 1431-2019 "Determination Method for Compressive Strength of Carbon Materials", the porosity was tested with reference to GB / T 24529-2009 "Determination Method for Apparent Porosity of Carbon Materials", the resistivity was tested with reference to GB / T 24525-2009 "Determination Method for Resistivity of Carbon Materials", the thermal conductivity was tested with reference to GB / T8722-2019 "Determination Method for Thermal Conductivity of Carbon Materials", and the thermal expansion coefficient was tested with reference to GB / T 3074.4-2016 "Method for Determination of Coefficient of Thermal Expansion (CTE) of Graphite Electrode", the test results are shown in Table 1:

[0095] Table 1

[0096]

[0097] It can be seen from Table 1 above that the graphite material for graphite boat sheets provided by the present invention has good mechanical properties, good electrical and thermal conductivity, extremely low porosity and thermal expansion coefficient, and is particularly suitable for the preparation material of graphite boat sheets, and has good application prospects.

[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing graphite material for graphite boat sheets, characterized in that: The following steps are involved: S1, pretreatment of natural flake graphite: purifying natural flake graphite and adding it into an acidic potassium permanganate solution for stirring and impregnation treatment, filtering, washing and drying after the treatment to obtain pretreated natural flake graphite; S2, preparation of modified flake graphite: adding the pretreated natural flake graphite in step S1 to deionized water, then adding zirconium oxychloride, stirring evenly, adding ammonia water, carrying out hydrothermal reaction, filtering, washing, and drying after the reaction is completed to obtain solid powder; then adding the solid powder to anhydrous ethanol, then adding γ-mercaptopropyltrimethoxysilane, stirring at 50-60° C. for 2-3 hours, then adding 1-dodecene and benzophenone, carrying out isothermal reaction under ultraviolet light, filtering, washing, and drying after the reaction is completed to obtain modified flake graphite; S3, preparation of a mixture: grinding petroleum coke and asphalt coke to obtain a mixed powder, then adding the mixed powder and carbon black into a kneading pot and mixing them evenly, performing a primary kneading process; then adding the modified flake graphite in step S2, mixing them evenly, performing a secondary kneading process, and obtaining a mixture; S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it twice to obtain abrasive; S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine for pressing to obtain a green body, and then calcining the green body to obtain a calcined material; S6, impregnation and carbonization: adding the roasted material in step S5 into an impregnation tank, evacuating the tank, and then adding molten medium-temperature asphalt for impregnation, and carbonizing the material after the impregnation to obtain a carbonized material; S7, graphitization: graphitizing the carbonized material in step S6 to obtain the graphite material for the graphite boat.

2. The preparation method according to claim 1, characterized in that: In step S1, the pH of the acidic potassium permanganate is 3-4, the concentration of potassium permanganate is 40-60 g / L, the temperature of the stirring immersion is 30-40° C., and the time is 2-4 hours.

3. The preparation method according to claim 1, characterized in that: In step S2, the mass concentration of the ammonia water is 10-15%, the mass ratio of the pretreated natural flake graphite, deionized water, zirconium oxychloride, and ammonia water is 50:800-1000:20-30:60-100, the temperature of the hydrothermal reaction is 140-170°C, and the time is 7-10h; the mass ratio of the solid powder, γ-mercaptopropyltrimethoxysilane, 1-dodecene, and benzophenone is 50:5-8:4-8:0.2-0.5, and the intensity of the ultraviolet light is 20-40W / m 2 The temperature of the isothermal reaction is 60-70°C and the time is 1-2h.

4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of petroleum coke to asphalt coke is 20:25-60, and the mass ratio of the mixed powder, carbon black and modified flake graphite is 45-80:10-20:15-30; the temperature of the first kneading treatment is 90-100°C, the time is 0.5-1h, and the temperature of the second kneading treatment is 160-180°C, and the time is 0.5-1h.

5. The preparation method according to claim 1, characterized in that: The particle size of the abrasive in step S4 is 5-15 μm.

6. The preparation method according to claim 1, characterized in that: The pressing pressure in step S5 is 90-130 MPa and the time is 1-2 hours; the calcination temperature is 750-850° C. and the time is 3-5 days.

7. The preparation method according to claim 1, characterized in that: In step S6, the vacuum is evacuated to 60-100 Pa, and the impregnation conditions are 190-210° C. and 4-7 MPa for 15-20 hours; the carbonization temperature is 1100-1300° C. and the time is 20-30 days.

8. The preparation method according to claim 1, characterized in that: The graphitization temperature in step S7 is 2500-2900° C. and the time is 30-40 days.

9. A graphite material for a graphite boat prepared by the method according to any one of claims 1 to 8.

10. Use of the graphite material according to claim 9 in preparing graphite boat sheets.

Citation Information

Patent Citations

  • Pretreatment method of graphite boat and modified graphite boat

    CN115287632A

  • Modified method of natural graphite material for lithium ion battery

    CN101214952A

  • Method for preparing high thermal conductivity graphite material

    CN101538036A